Analisis Pengelolaan Sampah Rumah Tangga Berbasis Masyarakat Di Kecamatan Marpoyan Damai Kota Pekanbaru - Lita Febriani; Yusni Ikhwan Siregar; Ridwan Manda Putra (Sistem Informasi, 2020)
The purpose of this study is to analyze the factors in community-based waste management and analyze the environmental, economic and social impacts of waste management in Marpoyan Damai District, Pekanbaru City. The approach of this research is quantitative analytic with cross sectional research design. The population in this study were all family heads in the Tangkerang Barat sub-district Marpoyan Damai Pekanbaru City as many as 4,345 households with a sample of 98 people. The results of this study are there is an influence between education (p value = 0.006), infrastructure (p value = 0.003), knowledge (p value = 0,000) with community participation in household waste management in Marpoyan Damai District, Pekanbaru City. The logistic regression analysis results found that the education variable has a value of p = 0.048 and an OR 2.888 which means that education has 2 times the risk of waste management. Infrastructure variable has a value of p = 0.001 and OR 6.838 which means that infrastructure has 6 times the risk of waste management. Knowledge variable has a value of p = 0,000 and OR 9,617 which means knowledge has 9 times the risk of waste management. The environmental impact of proper waste management is decreasing the volume of waste generation and environmental damage. Economically, there is currently no economic value to waste management, other than the public does not understand waste management that has economic value with 3R. Inadequate waste management causes low levels of public health, so people need to pay more for treatment. Socially, most people do not care about waste management and even though there is waste management it is still individual and not organized in an integrated way.